Biological roles of l‐carnitine in oocyte and early embryo development. Issue 10 (7th October 2021) - Li, Jiajian; Liu, Lingyan; Weng, Jing; Yin, Tai‐lang; Yang, Jing; Feng, Huai L.
Abstract: Poor oocyte quality is responsible for female infertility. Multiple studies have been carried out to find supplements to enhance oocyte quality and mitigate infertility problems. l ‐carnitine and its derivatives have diverse roles in developing oocytes and early embryos. This review focuses on the in vitro and in vivo studies that using l ‐carnitine alone or in combination with other supplements for oocyte quality enhancement. The key roles of l ‐carnitine in oocyte quality and embryo growth were summarized, and the underlying mechanism was also elucidated. l ‐carnitine helps in the lipid metabolism process by controlling the transfer of fatty acids to mitochondria for β‐oxidation. l ‐carnitine modulates glucose metabolism and enhances respiratory chain enzyme activity. Furthermore, it acts as an antioxidant to prevent oxidative damage and inhibit apoptosis, a signal in response to oxidative stress. Results show the potential of l ‐carnitine as a potential agent in assisted reproductive technology to improve oocyte quality and the subsequent embryonic development.